Slightly tempted - Balogh, Mary (Bedwyn Family, 2004)
Lady Morgan Bedwyn seems the perfect tool for the Earl of Rosthorn to use in seeking revenge, but when a shocking night of intimacy results in scandal -- and a melted heart for the Earl -- Morgan refuses the marriage he so badly wants.